2011
DOI: 10.1002/ibd.21577
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal alpha-defensin expression in pediatric inflammatory bowel disease1

Abstract: In this study no difference in alpha-defensin expression was found in the TI of CD children and controls. However, significant reduction of Tcf-4 in L1+L3 phenotype suggests that a possibly impaired PC differentiation may lead to altered HD5 and HD6 expression at some stage of disease. Additionally, substantially increased expression of alpha-defensins in the inflamed colonic mucosa of children with IBD raises the question for their potential involvement in modulating inflammation in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 29 publications
0
18
0
1
Order By: Relevance
“…Recognition of MDP by NOD2 drives the activation of the pro-inflammatory transcription factor NF-jB and mitogen-activated protein kinase (MAPK) [75,78]. The importance of NOD2 in intestinal disease is supported by studies that show variants in NOD2 gene to predispose individuals to Crohn's disease [79][80][81][82][83]. NOD2 was most commonly associated with a role in immune cells such as macrophages, dendritic cells, granulocytes [78,84,85], but has also been shown to be expressed in intestinal epithelial cells [34].…”
Section: Nod2/card15mentioning
confidence: 76%
“…Recognition of MDP by NOD2 drives the activation of the pro-inflammatory transcription factor NF-jB and mitogen-activated protein kinase (MAPK) [75,78]. The importance of NOD2 in intestinal disease is supported by studies that show variants in NOD2 gene to predispose individuals to Crohn's disease [79][80][81][82][83]. NOD2 was most commonly associated with a role in immune cells such as macrophages, dendritic cells, granulocytes [78,84,85], but has also been shown to be expressed in intestinal epithelial cells [34].…”
Section: Nod2/card15mentioning
confidence: 76%
“…However, these results might be influenced by serum anti-bacterial proteins (e.g. immunoglobulins and complement components) from mucosal bleeding, and by the increased secretion of antibacterial peptides such as defensins [42]. On the other hand, the effects of such factors can be omitted during the remission phase.…”
Section: Discussionmentioning
confidence: 99%
“…Increased colonic Paneth cells in IBD may be part of an adaptive reaction in which alpha defensins constitute a protective barrier that helps prevent secondary mucosal infection in already inflamed bowel [22]. Alternatively, it has been suggested that PCM in the colon may exacerbate or even initiate IBD there [23]. The interplay of factors is complex and the role of Paneth cells in the pathogenesis of colonic IBD remains unclear.…”
Section: Discussionmentioning
confidence: 99%